Multifunctional modular antenna for near‐field ultra‐high frequency radio frequency identification readers. Issue 8 (1st June 2016) - Michel, Andrea; Caso, Roberto; Buffi, Alice; Nepa, Paolo
Abstract : A multifunctional modular antenna suitable to be embedded into low‐profile ultra‐high frequency radio frequency identification desktop readers is designed, prototyped and characterised at system level. Two operating modes are foreseen. The first one allows for best performance right on the reader surface (reactive near‐field region), and exploits a spiral‐shaped travelling wave antenna (TWA) ended on a matched load and optimised ( spiral TWA configuration ). The second operating mode exhibits a field coverage up to a few decimetres away from the reader surface (radiative near‐field region), and takes advantage of the above spiral TWA that serially feeds a low‐gain resonating antenna. An array of two circularly polarised miniaturised patches is here considered for the resonating antenna. By means of a switch at the spiral TWA end, each one of the two operating modes can be selected on the basis of the application scenario of interest. Specifically, the spiral TWA configuration is suitable for tag writing operations, when the only tag that has to be encoded is most likely placed at the reader antenna centre. On the other hand, the modular antenna configuration allows the desktop reader to detect tags up to few decimetres, even in presence of stacked tagged objects.